The effect of physical properties on flame spread behavior for various paper/bagasse composition - Ramli, Afifah (2019)
Fire Safety Engineering is an application of science to improve the safety from the destructive effect of the fire. Paper is well known as a material that can easily catch fire. Nowadays, many researchers have been interested to produce paper by using other natural fiber to reduce the usage of wood as raw material for paper production. However, research on flame spread towards combination paper / natural fiber is still a lack of data. Inspiration from this, the behavior of downward flame spread over paper and bagasse is experimentally investigated. This experiment was conducted by using the specimen with different thickness and different composition of bagasse. Specimen thickness was chosen at 0.7mm, 1.4mm, 2. and 2.8mm; while for bagasse composition are 0%, 30%, 50%, 70% and 100%. Flame spread behavior for each specimen was videotaped by using a camera. The result showed that the flame spreads was with "U" pattern at the beginning of the combustion, but end up with different pattern according to thickness and composition of bagasse. It seen that flame spread rate decreases with increasing the thickness and composition of bagasse for the specimen. The result also shows that up to 70% bagasse, the flame spread rate is approximately constant even for different thickness. Result infers that the flame spread rate is influenced by not only bagasse composition, but also the density and the pyrolysis height; where pyrolysis height represents the area of the heat release continuity by fire source that has been removed. It shows that the flame spread rate decreases as the density increases. While for pyrolysis height, the higher the pyrolysis height the higher the flame spread rate.